Investigating the potential of GalR2 as a drug target for neuropathic pain. (April 2023) - Rich, Kirsty; Rehman, Samrina; Jerman, Jeff; Wilkinson, Graeme
Abstract: Neuropathic pain is a chronic and debilitating condition characterised by episodes of hyperalgesia and allodynia. It occurs following nerve damage from disease, inflammation or injury and currently impacts up to 17% of the UK population. Existing therapies lack efficacy and have deleterious side effects that can be severely limiting. Galanin receptor 2 (GalR2) is a G-protein coupled receptor (GPCR) implicated in the control and processing of painful stimuli. Within the nervous system it is expressed in key tissues involved in these actions such as dorsal root ganglia (DRG) and the dorsal horn of the spinal cord. Stimulation of GalR2 is widely reported to have a role in the attenuation of inflammatory and neuropathic pain. Several studies have indicated GalR2 as a possible drug target, highlighting the potential of specific GalR2 agonists to both provide efficacy and to address the side-effect profiles of current pain therapies in clinical use. A strong biological target for drug discovery will be well validated with regards to its role in the relevant disease pathology. Ideally there will be good translational models, sensitive probes, selective and appropriate molecular tools, translational biomarkers, a clearly defined patient population and strong opportunities for commercialisation. Before GalR2 can be considered as a drug target suitable for investment, key questions need to be asked regarding its expression profile, receptor signalling and ligand interactions. This article aims to critically review the available literature and determine the current strength of hypothesis of GalR2 as a target for the treatment of neuropathic pain. Graphical abstract: Unlabelled Image Highlights: Neuropathic pain impacts 17% of the UK population. Current treatments for neuropathic pain lack efficacy and have deleterious side effects. Galanin is increased in DRG following nerve injury. Agonism of the GalR2 receptor with Galanin may attenuate neuropathic pain.